The Implementation of E-government in Spatial Planning Licensing: A Study in Asmat Regency Government - Rumkorem, Rikover Alberth (KnE Social Sciences, 2025)
This paper investigates the implementation of e-government in the spatial planning licensing sector within the Asmat Regency Government. In light of national policies promoting digital transformation in public administration, this study highlights the specific dynamics, challenges, and impacts of such initiatives in remote and underdeveloped regions. Using a qualitative approach involving document analysis, interviews, and field observations, the research reveals both progress and limitations. While the e-government system has contributed to more transparent and efficient licensing processes, issues such as inadequate infrastructure, limited digital literacy, and system fragmentation persist. The findings show that the Asmat Regency has made initial steps in digitizing licensing processes through a basic online platform. However, the effectiveness of this system is hindered by uneven access to ICT infrastructure across its districts, a lack of skilled personnel to operate and maintain digital systems, and a public that is largely unfamiliar with digital platforms. In response, local government has taken initiatives such as mobile service units and digital literacy training. Nonetheless, broader support from national-level programs is essential to ensure long-term success. This study contributes to the discourse on e-government implementation in marginalized and geographically isolated regions, providing insights that may be applicable to other districts with similar challenges. It underscores the importance of contextual policy design, multi-stakeholder engagement, and integrated infrastructure development.